Recent advances in the quantitative understanding of friction stir welding - De, A.; DebRoy, T. (Автоматическая сварка, 2013)
Friction stir welding (FSW) is a relatively new welding process and its comprehensive understanding is still developing. While
the process is commercially used for aluminum and other soft alloys, its commercial application for the welding of hard alloys
will require development of cost-effective and durable tools. Here we review the recent progress made in numerical modeling
heat transfer and material flow with particular emphasis on optimizing tool dimensions and selection of welding conditions for
maximizing tool durability.